2018
DOI: 10.1371/journal.pone.0199655
|View full text |Cite
|
Sign up to set email alerts
|

When is enough, enough? Quantifying trade-offs between information quality and sampling effort for fishing gear selectivity data

Abstract: There is general pressure throughout the world’s fisheries for the industry to have greater involvement not only in the development of fishing gears but also in the testing and documentation of their effect. In the European Union, the Common Fisheries Policy of 2013, together with the proposed reform of the technical measures regulation, highlights the need for greater flexibility in fisheries through increased stakeholder involvement. To achieve this flexibility, there is a need for additional fishing gears a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…It has been demonstrated that the accuracy of selectivity studies for fishing gears would be affected by the number of fish caught and length measured in the sea trials [28,29]. The more fish is length measured, the less uncertainty will be obtained in the estimation of selective parameters.…”
Section: Plos Onementioning
confidence: 99%
“…It has been demonstrated that the accuracy of selectivity studies for fishing gears would be affected by the number of fish caught and length measured in the sea trials [28,29]. The more fish is length measured, the less uncertainty will be obtained in the estimation of selective parameters.…”
Section: Plos Onementioning
confidence: 99%
“…Current efforts to reduce negative fisheries impacts on a global scale include approaches such as bycatch reduction strategies ( Swimmer et al, 2011 ; O’Neill & Mutch, 2017 ; Veiga-Malta et al, 2018 ), bans on harvests of certain species ( Sherman et al, 2018 ), elimination of discards ( European Union, 2013 ), regulating exports related to non-sustainable fisheries ( Shiffman & Hueter, 2017 ), fishing regulatory closures for Vulnerable Marine Ecosystems (VME) in Areas Beyond National Jurisdiction (ABNJ) ( NEAFC, 2018 ), prohibition of destructive gear types for VMEs ( Auster et al, 2011 ), marine protected areas ( Hameed et al, 2017 ; Hastings, Gaines & Costello, 2017 ), and increased aquaculture production ( FAO, 2018 ; Froehlich, Gentry & Halpern, 2017 ). Implementation of conservation measures such as large-scale marine protected areas can pose challenges for nations that close off areas of their waters; however cross-jurisdictional management with transferable fishing rights has been proposed as a potentially viable market-based solution to promote transboundary cooperation in these situations ( Villaseñor-Derbez, Lynham & Costello, 2020 ).…”
Section: Reviewmentioning
confidence: 99%
“…Current efforts to reduce negative fisheries impacts on a global scale include approaches such as bycatch reduction strategies (Swimmer et al, 2011;O'Neill & Mutch, 2017;Veiga-Malta et al, 2018), bans on harvests of certain species (Sherman et al, 2018), elimination of discards (European Union, 2013), regulating exports related to non-sustainable fisheries (Shiffman & Hueter, 2017), fishing regulatory closures for Vulnerable Marine Ecosystems (VME) in Areas Beyond National Jurisdiction (ABNJ) (NEAFC, 2018), prohibition of destructive gear types for VMEs (Auster et al, 2011), marine protected areas (Hameed et al 2017;Hastings et al 2017), and increased aquaculture production (FAO 2018;Froehlich et al 2017). Implementation of conservation measures such as large-scale marine protected areas can pose challenges for nations that close off areas of their waters; however cross-jurisdictional management with transferable fishing rights has been proposed as a potentially viable market-based solution to promote transboundary cooperation in these situations (Villaseñor-Derbez et al 2020).…”
Section: Introductionmentioning
confidence: 99%